2018
DOI: 10.1002/adfm.201801095
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerized Triazole‐Based Glassy Polymer Networks with Superior Tensile Toughness

Abstract: Photopolymerization is a ubiquitous, indispensable technique widely applied in applications from coatings, inks, and adhesives to thermosetting restorative materials for medical implants, and the fabrication of complex macro-scale, microscale, and nanoscale 3D architectures via additive manufacturing. However, due to the brittleness inherent in the dominant acrylate-based photopolymerized networks, a significant need exists for higher performance resin/oligomer formulations to create tough, defect-free, mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 61 publications
0
39
0
Order By: Relevance
“…[ 10–14 ] Thiol‐ene‐based polymers are one class of materials that have drawn significant attention owing to their controllable, tunable mechanical properties. [ 15–17 ] This is generally attributed to more uniform molecular networks in thiol‐ene materials, resulting from the step‐growth mechanism of the polymerization reaction. [ 18,19 ] Thiol‐ene materials have already shown promise for applications including use in adhesives, electronics, and as biomaterials.…”
Section: Figurementioning
confidence: 99%
“…[ 10–14 ] Thiol‐ene‐based polymers are one class of materials that have drawn significant attention owing to their controllable, tunable mechanical properties. [ 15–17 ] This is generally attributed to more uniform molecular networks in thiol‐ene materials, resulting from the step‐growth mechanism of the polymerization reaction. [ 18,19 ] Thiol‐ene materials have already shown promise for applications including use in adhesives, electronics, and as biomaterials.…”
Section: Figurementioning
confidence: 99%
“…[ 26–28 ] Recent work demonstrated that glassy networks with high T g are obtained due to the formation of rigid, thermally and chemically stable triazole moieties present at high concentrations within the network ( Scheme A). [ 29–31 ] Although glassy polymers are stiff with limited mobility, localized segmental motion still occurs and requires little free volume to persist at temperatures well below T g . [ 32–34 ] As was previously proven, such local mobility at the bond level is adequate to change the bond distance and cause bond reconfiguration in glassy systems as has been demonstrated, for example, repeatedly in azobenzene‐containing polymers.…”
Section: Methodsmentioning
confidence: 99%
“…The CuAAC reaction has also been applied to the formation of step-growth bulk photopolymer networks, where the photopolymerization generates triazole adducts that are thermally, chemically, and mechanically stable [146]. Triazole structures, especially in a densely cross-linked network, substantially enhance the mechanical stiffness and strength of these materials during the polymerization.…”
Section: Preparation Of Thermosets By Azide-yne Polymerizationmentioning
confidence: 99%